Multi-rotor control formulation and simulation for parcel delivery - Nguyen, Trinh Tuan Anh (Nanyang Technological University, 2024)
This study presents the formulation and simulation of a multi-rotor control system, specifically designed for optimizing parcel delivery. Leveraging the capabilities of Simscape within the MATLAB environment, the project models a quadrotor UAV (Unmanned Aerial Vehicle) tasked with urban parcel delivery. Our research objectives focused on validating the UAV's physical and control system dynamics through extensive simulations, ensuring accurate payload handling and navigation efficiency.